La mediación como medio alternativo de solución de conflictos en la reparación económica a la víctima de violencia intrafamiliar - Serrado Palacios, Marlene (2018)
The present research aims to establish mediation as an alternative means of resolving conflicts in the economic reparation to the victim of domestic violence, through the collaboration of victims and perpetrators and thus to establish mediation as an alternative in the economic reparation of Affected party and thus to promote the peaceful way in the solution of intra-family violence conflicts. The mediation in the economic reparation to the victim are the guidelines in which the investigation will be governed according to the inhabitants and the Judicial System of the Milagro Canton. In order to carry out the research, different methods were used to determine the magnitude and its incidence of the problem, such as the qualitative and quantitative approach, exploratory, deductive, descriptive and bibliographic information, which would provide a clear idea for the project proposal to Shape………